C Curriculum Innovation In An Effort To Improve The Quality Of Education At SMP Negeri 1 Sabang: Curriculum Innovation In An Effort To Improve The Quality Of Education At SMP Negeri 1 Sabang - Azizah (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study aims to describe and analyze how curriculum innovation is an effort to improve the quality of education at SMP Negeri 1 Sabang. A relevant and innovative curriculum is the key to improving the quality of graduates who are able to compete in the era of globalization. In the framework of curriculum innovation, SMP Negeri 1 Sabang has a Bilingual Class program which is one of the superior class programs. Learning in this class uses 2 languages ​​(Indonesian and English) as an introduction to learning, especially for 3 subjects, namely Science, Mathematics, and English. In addition, there are routine daily, weekly, monthly, semester, and annual programs, enrichment programs for Science, Mathematics, English, reading and writing the Quran and the Masailal Muhtadi book and the habit of daily communication in schools must use English. This study uses a qualitative descriptive approach. Data collection techniques are carried out by observation, interviews, and documentation studies. Data analysis techniques used include data condensation, data presentation, and drawing conclusions. The results of the study to implement innovation at SMP Negeri 1 Sabang, were carried out through stages, namely planning, implementation, and evaluation. There are advantages and opportunities that SMP Negeri 1 Sabang has that become enthusiasm and motivation but there are also limitations that must be found solutions to run the Biligual Class program. The Biligual Class program has been running well in order to improve the quality of education at SMP Negeri 1 Sabang. This can be seen from the school's achievements, the graduation rate of Biligual Class program students at Favorite High Schools in Banda Aceh and SMA Negeri 1 Sabang, and the improvement of character and English language skills.